Phenomenology and the ideal of science. In the century of article Philosophy as Rigorous Science (2011)
Did Husserl give up the ideal of the rigorous science —exposed and brought to its maximum demand in the Article for Logos Journal in 1911? Or, in the contrary, does this ideal of rigorous science lead the whole Husserl’s work, and is this ideal the key of